2010
DOI: 10.1002/mame.200900215
|View full text |Cite
|
Sign up to set email alerts
|

Switchable Wettability of Thermo‐Responsive Biocompatible Nanofibrous Films Created by Electrospinning

Abstract: Thermo‐responsive PNIPAAm/PLLA nanofibrous films with tunable surface morphologies and better biocompatibility were prepared by electrospinning technique. The electrospun composite films possessed a “bead‐on‐string” structure. The wettability of nanofibrous films was observed by water CA measurements. The results showed that the electrospinning process and addition of PLLA did not change the thermo‐sensitivity of PNIPAAm. The wettability of electrospun PNIPAAm/PLLA composite films could switch from superhydrop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
51
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(53 citation statements)
references
References 48 publications
(113 reference statements)
0
51
0
2
Order By: Relevance
“…[26][27] Previous reports showed that PNIPAAm and poly(L-lactide) (PLLA) mixture with tunable surface morphologies can be increased by spinning from N-N-dimethylformamide (DMF). [28] Ethyl cellulose (EC) is a kind of polysaccharides with a good film-forming ability, hydrophobicity and biocompatibility. Therefore, it is widely used in nanofibers preparation, either blended or coaxial electrospun, for application in drug-release fields.…”
Section: Introductionmentioning
confidence: 99%
“…[26][27] Previous reports showed that PNIPAAm and poly(L-lactide) (PLLA) mixture with tunable surface morphologies can be increased by spinning from N-N-dimethylformamide (DMF). [28] Ethyl cellulose (EC) is a kind of polysaccharides with a good film-forming ability, hydrophobicity and biocompatibility. Therefore, it is widely used in nanofibers preparation, either blended or coaxial electrospun, for application in drug-release fields.…”
Section: Introductionmentioning
confidence: 99%
“…The outflowing of polymer solutions with specific viscosity, conductivity, and surface tension through a thin capillary in the presence of an externally applied electric field results in the production of micro-or nanoparticles or fibers of various sizes and shapes. 19,20 Multicompartmental characteristics of the anisotropic architectures make them suitable for a number of intriguing applications, including switchable display devices, 21 a colloidal stabilizer at an interface of two immiscible solutions, 22 selfpropelled motors, 23 optical sensors, 24 and spontaneous assembly for complex structures. 25 In addition, multicompartmental nanofibers with core-shell [26][27][28][29] and side-by-side 30,31 structures have been explored for drug delivery systems and tissue engineering scaffolds.…”
Section: Introductionmentioning
confidence: 99%
“…[62,63] For more complex patterned surfaces or hierarchical structured surfaces, laser treatment and electrospinning methods are usually applied. [64][65][66] Chemical methods can provide more complex structures with precise control in nanoscale. Hydrothermal methods can produce single crystals with precisely shape-controlled nanostructures, while anodization can produce large-area modifications of nanoholes, nanotubes, nanowires, etc.…”
Section: Introduction Of the Fabrication Methods To Generate Slpl Intmentioning
confidence: 99%